Sistem Pendukung Keputusan untuk Mengevaluasi Kinerja Karyawan pada PT Tempo Scan Pasific dengan Metode Analytical Hierarchy Process (AHP) - Dian Mayasari (Jurnal Publikasi Manajemen Informatika, 2024)
Employee performance evaluation is a crucial aspect of human resource management, as it helps maintain and enhance employee productivity while influencing decisions related to promotions, salary increases, and career development. This study aims to develop a decision support system using the Analytical Hierarchy Process (AHP) method to assist decision-making teams in evaluating employee performance objectively, systematically, and meritocratically. The system is designed to minimize potential errors in the evaluation process, enabling more accurate and fair assessments in identifying the best employees. Consequently, the findings of this study are expected to contribute to the overall improvement of the company's performance in the future.